2005
DOI: 10.1089/aid.2005.21.379
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Region within the Cytoplasmic Domain of the Subtype B Vpu Protein of Human Immunodeficiency Virus Type 1 (HIV-1) That Is Responsible for Retention in the Golgi Complex and Its Absence in the Vpu Protein from a Subtype C HIV-1

Abstract: The structure of the Vpu protein of human immunodeficiency virus type 1 (HIV-1) is composed of a short Nterminal domain (NTD), a transmembrane domain (TM), and a cytoplasmic domain (CD). Previous studies have shown that the Vpu protein from subtype B HIV-1 is transported predominantly to the rough endoplasmic reticulum (RER)/Golgi complex compartments of the cell and is not incorporated into virions. Using a previously described VpuEGFP reporter system in which the Vpu protein was fused to the gene for enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 40 publications
10
60
0
Order By: Relevance
“…The cellular distribution of viperin and its colocalization with EIAV Gag would positively support our finding that the TGN is involved in EIAV Gag assembly. Previous studies have shown that the HIV-1 Vpu protein is predominantly transported to RER/Golgi complex compartments (33). In our study, EIAV particles localized adjacent to the RER, and EIAV Gag multimers were surrounded by Vpu proteins (Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The cellular distribution of viperin and its colocalization with EIAV Gag would positively support our finding that the TGN is involved in EIAV Gag assembly. Previous studies have shown that the HIV-1 Vpu protein is predominantly transported to RER/Golgi complex compartments (33). In our study, EIAV particles localized adjacent to the RER, and EIAV Gag multimers were surrounded by Vpu proteins (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…4B). Previous studies have shown that the HIV-1 Vpu protein is transported predominantly to RER/Golgi complex compartments (33). Thus, we cotransfected Vpu-HA with EIAV Gag-GFP or HIV-1 Gag-GFP into 293T cells and evaluated their cellular distribution.…”
Section: Eiav Gag Proteins Accumulate In the Trans-golgi Network (Tgn)mentioning
confidence: 96%
“…The prototypical BST-2 antagonist is the HIV-1 accessory protein Vpu (1,2). Vpu localizes primarily in endosomes and the trans-Golgi network (4,5), where it is thought to interact with BST-2. Vpu expression results in reduced levels of BST-2 on the host cell membrane (6 -8) and either the degradation (9 -12) or the sequestration of the host factor in intracellular compartments (7,13), leading to increased virus release.…”
mentioning
confidence: 99%
“…Although Vpu appears to act on a host protein that exerts its restricting activity on HIV particle release at the cell surface, the most-studied subtype B Vpu was found to localize predominantly in the trans-Golgi network (TGN) and to a lesser extent in the ER and the recycling endosomes (23,42).…”
mentioning
confidence: 99%
“…However, in contrast to the prototypical subtype B Vpu, the subtype C Vpu protein was found to localize both at the plasma membrane and in the Golgi complex (23). While ER localization is required for CD4 degradation, the artificial retention of Vpu in the ER appears to interfere with the enhancement of viral particle release, suggesting that Vpu needs to reach a post-ER compartment to mediate this function (32).…”
mentioning
confidence: 99%